2014
DOI: 10.1155/2014/435208
|View full text |Cite
|
Sign up to set email alerts
|

Haemorrhagic Presentation of a Craniopharyngioma in a Pregnant Woman

Abstract: Objective. Craniopharyngioma is a rare tumour, and, consequently, acute clinical presentation and diagnosis, during pregnancy, of this pathology are quite difficult to find. Only few cases are reported in the literature, and no one describes these two conditions in association. Methods. We report a particular case of craniopharyngioma presenting both of the above conditions. Results. The patient was successfully operated with endoscopic technique. Conclusions. Rare and difficult cases, created by the superposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…We conducted a review of the literature and found several reports of craniopharyngioma associated with hydrocephalus or hemorrhage (►Table 2). 1,5,[8][9][10][11][12] Obstructive hydrocephalus was identified at diagnosis in 49 (45.4%) of 108 patients with craniopharyngioma, but none had nonobstructive hydrocephalus. 12 In our series, obstructive hydrocephalus was identified in 22 patients at diagnosis, and 8 of them (36.4%) required a VP shunt even after tumor removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a review of the literature and found several reports of craniopharyngioma associated with hydrocephalus or hemorrhage (►Table 2). 1,5,[8][9][10][11][12] Obstructive hydrocephalus was identified at diagnosis in 49 (45.4%) of 108 patients with craniopharyngioma, but none had nonobstructive hydrocephalus. 12 In our series, obstructive hydrocephalus was identified in 22 patients at diagnosis, and 8 of them (36.4%) required a VP shunt even after tumor removal.…”
Section: Discussionmentioning
confidence: 99%
“…Minor bleeding into the CSF is even more uncommon. 1,5 We report our surgical series of consecutive patients with craniopharyngioma who presented with hydrocephalus.…”
Section: Introductionmentioning
confidence: 99%
“…There are two histological types -papillary and adamantinomatous. 1 Adamantinomatous tumour cosists of cysts and dystrophic calcifications 5 and may develop in all ages. 4 Papillary type is usually without cyst and calcifications 1 and occurs almost exclusively in children 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Craniopharyngiomas are rare solid or mixed solid -cystic tumors that arise from remnants of Rathke's pouch. Mostly it is benign in nature 1 and consists of 3% of all intracranial neoplasms. 2 The incidence of craniopharyngioma was 0.13 per 100,000 person's year 3 and equally common in males and females.…”
Section: Introductionmentioning
confidence: 99%
“…There are two histological types -papillary and adamantinomatous. 1 Adamantinomatous tumour cosists of cysts and dystrophic calcifications 5 and may develop in all ages. 4 Papillary type is usually without cyst and calcifications 1 and occurs almost exclusively in children 6 .…”
Section: Introductionmentioning
confidence: 99%